Dampak Bantuan Insentif Pemerintah Bagi Pelaku Usaha Pariwisata dan Ekonomi Kreatif - Somadi, Somadi; Amalia Sartika, Siti N. (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
The Covid-19 pandemic has had a huge impact on the tourism sector, causing a decrease in foreign exchange receipts and economic contributions, a decrease in room occupancy rates, a decrease in income, business closures, and other impacts. To maintain business continuity in the tourism sector, the Government issued a Government Incentive Assistance Policy. However, the distribution and impact of this policy is difficult to know, due to the lack of transparency provided by the Government. For this reason, the aim of this research is to determine the distribution and impact of Government Incentive Assistance for tourism and creative economy entrepreneurs. Based on the results of the analysis, the amount of Government Incentive Assistance distributed in 2020 was IDR 25,980,947,161,- with a total of 232 business actors, while the amount of Government Incentive Assistance distributed in 2021 amounted to IDR 60,000,000,000,- with the number of recipients as many as 1,000 business actors. The impacts of Government Incentive Assistance include increasing business profits, determining location targets, demographics, adjusting trends in the products offered, and being able to survive bankruptcy by covering business operational costs in the next few months